2008
DOI: 10.1016/j.jesp.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

When approach motivation and behavioral inhibition collide: Behavior regulation through stimulus devaluation

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
228
7
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(259 citation statements)
references
References 41 publications
22
228
7
2
Order By: Relevance
“…Second, unlike the study by Verbruggen and Logan (2008) were responses to neutral stimuli had to be repeatedly inhibited, participants in this study were repeatedly confronted with highly rewarding food stimuli that automatically elicit a motivational approach response as well as positive effect. Consequently, repeatedly inhibiting responses toward a food product could have disrupted action preparation to obtain the food product (e.g., motivational approach tendencies; Veling & Aarts, in press) and/or reduced the reward value of the food product (Veling & Aarts, 2009;Veling, Holland, & van Knippenberg, 2008). Importantly, both possibilities can explain why repeatedly stopping responses to food is effective for participants with low baseline inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…Second, unlike the study by Verbruggen and Logan (2008) were responses to neutral stimuli had to be repeatedly inhibited, participants in this study were repeatedly confronted with highly rewarding food stimuli that automatically elicit a motivational approach response as well as positive effect. Consequently, repeatedly inhibiting responses toward a food product could have disrupted action preparation to obtain the food product (e.g., motivational approach tendencies; Veling & Aarts, in press) and/or reduced the reward value of the food product (Veling & Aarts, 2009;Veling, Holland, & van Knippenberg, 2008). Importantly, both possibilities can explain why repeatedly stopping responses to food is effective for participants with low baseline inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic processes may effectively turn the confrontation with freshly baked cookies from an effortful, difficult task into a non-effortful, easy task that no longer requires self-regulatory resources (Dewitte, 2013). If successful, weight regulators (a) automatically activated a dieting goal upon exposure to the cookies (Fishbach et al, 2003;Papies et al, 2008), (b) automatically devalued the "forbidden fruit" cookies (Veling, Holland, & van Knippenberg, 2008), and (c) turned their attention away from them (Friese, Bargas-Avila, Hofmann, & Wiers, 2010;Mogg, Bradley, Hyare, & Lee, 1998), then the tempting cookies would not be tempting anymore, making it easy after all to withstand and act in line with the dieting goal.…”
Section: Discussionmentioning
confidence: 99%
“…Lenartowizc et al, 2011;Verbruggen & Logan, 2008b) but also reduces its hedonic value and motivational incentive (e.g. Ferrey et al, 2012;Houben et al, 2012;Kiss et al, 2008;Raymond et al, 2003;Veling et al, 2008). Our interpretation of this is that when a distractor or no-go/stop stimulus becomes associated with an avoidance/aversive centre, then presentation of it will directly activate the avoidance/aversive centre, which in turn will suppress activation of the approach/appetitive centre (cf.…”
Section: Integration: Inhibition and Associationmentioning
confidence: 93%
“…These effects could be mediated by devaluation of the stimuli that were associated with stopping (e.g. Houben et al, 2012;Kiss, Raymond, Westoby, Nobre, Eimer, 2008;Veling, Holland, and van Knippenberg, 2008). Ferrey, Frischen, and Fenske (2012) showed that stop associations not only impact on the hedonic value of the stimuli associated with stopping but also on their behavioral incentive.…”
Section: What Is Learned During Conditioning Of Inhibitory Control?mentioning
confidence: 99%